Creating Continuity of Care Within Student-Run Free Clinics - Jaeger, Alexandra; Shah, Rahi R; Pavia, Jonathan; Martin, Kellan J; Silber, Riley M; Scott, Serena (Journal of Student-Run Clinics, 2024)
Student-run free clinics (SRFC) play an important role in filling gaps in the healthcare system by providing accessible, cost-free care to underserved populations. Continuity of care (CoC) can improve patient outcomes, but challenges such as inconsistent volunteer participation and patient follow-up can make CoC difficult to implement in SRFCs. The authors acknowledge the deficiencies in existing literature guiding SRFCs and highlight a systematic model to address barriers to CoC. This article proposes a structured CoC model for SRFCs, encompassing three levels: micro (patient-provider relationships), meso (clinic structure and volunteer management), and macro (coordination with external healthcare facilities). These levels aim to streamline patient-provider interactions, optimize clinic operations, and coordinate care beyond clinic visits. Some suggested strategies include fostering patient-provider trust through telehealth follow-ups, improving clinic organization with shared electronic medical records (EMRs), mitigating volunteer turnover with consistent leadership and team meetings, and partnering with local pharmacies. The implementation section explores limitations, including resource constraints and adaptability challenges, and proposes evaluation measures like tracking follow-up rates and collecting patient feedback to gauge the model’s efficacy. This structured approach offers a framework adaptable to SRFCs’ specific needs to enhance CoC and improve the overall quality of care patients receive.